How Sex Ed Fails People With Periods - Purvis, Dara E. (Columbia Journal of Gender and Law, 2021)
Long before I taught law students the intricacies of statutes, I taught junior high school students sex education. It was a part-time job while I was in college in Los Angeles, through a program with Planned Parenthood that provided a two-week curriculum in public junior high schools. Today I joke that it gave me my unflappable nature in the classroom—if you can tell preteens about syphilis, nothing that happens in a law school classroom will break your concentration—but it also gave me an indelible memory of how far sex ed in America has to go. During our training, one of my fellow teachers referred in passing to how annoying it was to change her tampon every time she had to urinate. She was a bright college student and engaged with reproductive work enough that she successfully applied to work at Planned Parenthood. Yet, she didn’t know that the vagina and urethra were different anatomical structures.